2021
DOI: 10.1016/j.amsu.2021.102482
|View full text |Cite
|
Sign up to set email alerts
|

Role of adipose mesenchymal stem cells and secretome in peripheral nerve regeneration

Abstract: The use of stem cells is a breakthrough in medical biotechnology which brings regenerative therapy into a new era. Over the past several decades, stem cells had been widely used as regenerative therapy and Mesenchymal Stem Cells (MSCs) had emerged as a promising therapeutic option. Currently stem cells are effective therapeutic agents againts several diseases due to their tissue protective and repair mechanisms. This therapeutic effect is largely due to the biomolecular properties including secretomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 81 publications
0
21
0
Order By: Relevance
“…Thus, the application of the secretome as a cell-free therapeutic approach may have benefits in promoting nerve regeneration, with clinical effects that involve immunomodulation at the site of injury, pro-vasculogenic effects, modulation of the different phases of Wallerian degeneration, increase in the thickness of the myelin sheaths, increase in the number and organization of nerve fibers, and decrease in the phenomena of fibrosis and exuberant scarring [ 22 ]. In addition to its potential direct effects on the promotion of peripheral nerve regeneration, the use of secretome as a therapeutic option has several technical advantages over the direct administration of cells: there are no concerns or limitations associated with the survival of MSCs after transplantation; the absence of proteins present on the cell surface decreases the immunogenic potential and the rejections after administration; the secretome can be stored for long periods of time as a ready-to-use and off-the-shelf product, and can be used when necessary without the need to expand large amounts of cells that can undergo phenotypic changes and lose therapeutic potential along the passages, in addition to not requiring the use of potentially toxic cryoprotectants; large amounts of secretome can be faster produced in bioreactors, increasing the efficiency of the process; the secretome can be modified and adapted for each clinical need [ 8 , 22 , 34 ]. Thus, there is a great clinical and scientific interest in developing regenerative therapies based on the administration of the cell secretome, as a whole or based on its constituent components, such as microvesicles and exosomes [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the application of the secretome as a cell-free therapeutic approach may have benefits in promoting nerve regeneration, with clinical effects that involve immunomodulation at the site of injury, pro-vasculogenic effects, modulation of the different phases of Wallerian degeneration, increase in the thickness of the myelin sheaths, increase in the number and organization of nerve fibers, and decrease in the phenomena of fibrosis and exuberant scarring [ 22 ]. In addition to its potential direct effects on the promotion of peripheral nerve regeneration, the use of secretome as a therapeutic option has several technical advantages over the direct administration of cells: there are no concerns or limitations associated with the survival of MSCs after transplantation; the absence of proteins present on the cell surface decreases the immunogenic potential and the rejections after administration; the secretome can be stored for long periods of time as a ready-to-use and off-the-shelf product, and can be used when necessary without the need to expand large amounts of cells that can undergo phenotypic changes and lose therapeutic potential along the passages, in addition to not requiring the use of potentially toxic cryoprotectants; large amounts of secretome can be faster produced in bioreactors, increasing the efficiency of the process; the secretome can be modified and adapted for each clinical need [ 8 , 22 , 34 ]. Thus, there is a great clinical and scientific interest in developing regenerative therapies based on the administration of the cell secretome, as a whole or based on its constituent components, such as microvesicles and exosomes [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the application of the secretome as a cell-free therapeutic approach may have benefits in promoting nerve regeneration, with clinical effects that involve immunomodulation at the site of injury, pro-vasculogenic effects, modulation of the different phases of Wallerian degeneration, increase in the thickness of the myelin sheats, increase in the number and organization of nerve fibers and decrease in the phenomena of fibrosis and exuberant scarring [20]. In addition to its potential direct effects on the promotion of peripheral nerve regeneration, the use of secretome as a therapeutic option has several technical advantages over the direct administration of cells: there are no concerns or limitations associated with the survival of MSCs after transplantation; the absence of proteins present on the cell surface decreases the immunogenic potential and the rejections after administration; the secretome can be stored for long periods of time as a ready-to-use and off-the-shelf product, and can be used when necessary without the need to expand large amounts of cells that can undergo phenotypic changes and lose therapeutic potential along the passages, in addition to not requiring the use of potentially toxic cryoprotectants; large amounts of secretome can be faster produced in bioreactors, increasing the efficiency of the process; the secretome can be modified and adapted for each clinical need [6,20,32]. Thus, there is a great clinical and scientific interest in developing regenerative therapies based on the administration of the cell secretome, as a whole or based on its constituent components such as microvesicles and exosomes [33].…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that an intravenous injection of either AT-MSCs or AT-MSC-CM reverted neuropathic hypersensitivity, reduced inflammation, and prevented the loss of skin innervation. An excellent review concerning the role of AT-MSCs and their secretome in peripheral nerve regeneration processes was presented very recently by Sumarwoto et al [ 93 ].…”
Section: At-mscs and Their Derivatives: Contribution To Regenerative ...mentioning
confidence: 99%